History and Urban Primacy: The Effect of the Spanish Reconquista on Muslim Cities - Rafael Gonzalez-Val; David Cuberes (European Regional Science Association (ERSA), 2013)
This paper aims to study the effect of a major historical event on the Spanish city size distribution, the Spanish Reconquista. This was a long military campaign that aimed to expel Muslims from the Iberian Peninsula. The process started in the early 1200s and ended around 1500, when the entire peninsula was brought back under Christian rule. The Reconquista had a major effect on the evolution of the Muslim and Christian populations during this period and offers a unique ?quasi-natural? experiment. The Reconquista dramatically decreased the population of the three main cities of the Moorish Caliphate - Granada, Cordoba, and Seville. This represents a very particular shock in the sense that these were cities with a vast majority of Muslim population, which was then replaced by Christian residents. Using a methodology closely related to Nitsch (2003) we show that the effect of the Reconquista on both the relative size of these three cities was indeed dramatic and that it cannot be simply explained by similar trends in other important national or international cities. Granada lost 53% of its population during the 1300-1800 period, whereas the figures for Cordoba and Seville were 33% and 7%, respectively. These impressive population drops are still present even after controlling for a large set of country and city-specific socioeconomic indicators. We interpret these results as suggestive that the Spanish Reconquista shock had permanent effects, and therefore, in the context studied here, history does not matter for city growth. Our results suggest that the locational fundamentals that made these three cities the most populated ones in the Peninsula for about 500 years ceased to be crucial growth determinants once Christians took control of them.
Keywords: 330; urban primacy; locational fundamentals; city growth; lock-in effects